2018
DOI: 10.1016/j.ijrobp.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Edema After Single-Fraction or Multifraction Stereotactic Radiosurgery for Meningioma: A Critical Review

Abstract: The variability in risks of edema and in factors impacting those risks is likely a result of differences across studies in the clinicopathologic characteristics of the patient populations, as well as differences in treatment modalities and SRS planning and delivery parameters. More studies on pooled populations, grouped by potential prognostic factors such as tumor location and prior therapy, are needed to better understand dosimetric and nondosimetric factors predictive of edema risk after SRS for meningioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 45 publications
(175 reference statements)
2
24
0
Order By: Relevance
“…Sheehan et al 38 reported on 212 patients who underwent GKRS for parasagittal and parafalcine meningiomas, of whom 11 patients (5.2%) had new or worsening peritumoral edema during a median follow-up period of 19.6 months (range 6-158 months). In a multicenter study, Milano et al 26 analyzed the follow-up data of SRS on the treatment of non-skull base meningiomas and indicated that the incidence of peritumoral edema ranged from 5% to 43% within 3-9 months following SRS. The results of these reports support the consensus that GKRS is a safe and effective treatment choice for intracranial benign meningiomas due to its low morbidity and mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Sheehan et al 38 reported on 212 patients who underwent GKRS for parasagittal and parafalcine meningiomas, of whom 11 patients (5.2%) had new or worsening peritumoral edema during a median follow-up period of 19.6 months (range 6-158 months). In a multicenter study, Milano et al 26 analyzed the follow-up data of SRS on the treatment of non-skull base meningiomas and indicated that the incidence of peritumoral edema ranged from 5% to 43% within 3-9 months following SRS. The results of these reports support the consensus that GKRS is a safe and effective treatment choice for intracranial benign meningiomas due to its low morbidity and mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiosurgery for the treatment of brain metastases can lead to higher local control rates and lower radiation doses to surrounding normal brain tissue, which plays an important role in the treatment of brain metastases. However, for patients with obvious cerebral edema, stereotactic radiosurgery may induce or aggravate cerebral edema, which cause poor tolerance to this treatment. Hence, it is necessary to pretreat edema before treatment with stereotactic radiosurgery (SRS).…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, several previously reported risk factors for PTBE after radiosurgery for meningioma were not included for the study. These include adjacency to vein or sinus, tight vs smooth brain-tumor interface, plasma levels of vascular endothelial growth factor, or a few others [5]. Lastly, the small number of cases may have reduced the statistical power and validation.…”
Section: Fig 2 Comparisons Of Age Mean Frontal Skull Hu Value Gtv mentioning
confidence: 99%
“…Previously, several risk factors associated with peritumoral brain edema (PTBE) after radiosurgery in meningioma were reported. These include greater radiation dose, greater tumor size or volume, tumor location, brain-tumor interface, no prior resection for meningioma, and presence of pretreatment edema [5]. Disruption of the tumor-brain barrier in meningioma plays a critical role in the development of PTBE [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation